2009
DOI: 10.1371/journal.pntd.0000508
|View full text |Cite
|
Sign up to set email alerts
|

Skeeter Buster: A Stochastic, Spatially Explicit Modeling Tool for Studying Aedes aegypti Population Replacement and Population Suppression Strategies

Abstract: BackgroundDengue is the most important mosquito-borne viral disease affecting humans. The only prevention measure currently available is the control of its vectors, primarily Aedes aegypti. Recent advances in genetic engineering have opened the possibility for a new range of control strategies based on genetically modified mosquitoes. Assessing the potential efficacy of genetic (and conventional) strategies requires the availability of modeling tools that accurately describe the dynamics and genetics of Ae. ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
211
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(215 citation statements)
references
References 46 publications
2
211
1
1
Order By: Relevance
“…Uncertainty analysis 25 on a stochastic spatial model of Ae. aegypti population dynamics 26 confirmed that current parameters estimates related to larval density dependence are associated with a large portion of the uncertainty for model-based predictions of mosquito population density. Increasing the amount of field data on density dependence in larval populations would help reduce uncertainty in model predictions of population densities and help better understand the impact of control methods on dengue virus infections.…”
Section: Introductionmentioning
confidence: 52%
“…Uncertainty analysis 25 on a stochastic spatial model of Ae. aegypti population dynamics 26 confirmed that current parameters estimates related to larval density dependence are associated with a large portion of the uncertainty for model-based predictions of mosquito population density. Increasing the amount of field data on density dependence in larval populations would help reduce uncertainty in model predictions of population densities and help better understand the impact of control methods on dengue virus infections.…”
Section: Introductionmentioning
confidence: 52%
“…The conclusion from this analysis is that modifier loci can easily select alleles that affect the population dynamics, and when they occur in stable equilibria, they generally are in linkage disequilibrium with the driven locus. The very rapid fixation of MCR may preclude the invasion of such modifiers, but in any case there is already machinery for analysis of such modifiers (Rasgon and Gould 2005;Magori et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…aegypti is the lack of adequate data for validation. Most models seek to represent the temporal dynamic response to climate and endogenous forces (Focks et al, 1993;Ferreira and Yang, 2003;Williams et al, 2013), while others consider the spatial-temporal dynamic by introducing dispersal mechanisms (Otero, Schweigmann and Solari, 2008;Magori et al, 2009;Almeida et al, 2010).…”
Section: Population Modellingmentioning
confidence: 99%
“…Dispersal between cells is modulated by the availability of breeding sites. A similar approach considered both the spatial distribution of breeding sites and the dynamics of the aquatic stage of the mosquitoes (larvae and pupae) (Focks et al, 1993;Magori et al, 2009).…”
Section: Population Modellingmentioning
confidence: 99%